2023
DOI: 10.1177/21582440231166601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Brief Mindfulness Training on Anxiety, Depression, and Subjective Happiness of the First-Year Psychology Students in Russia: Pilot Case Study of Ural Federal University

Abstract: According to Russian researchers, university studies is among the most stressful activities for a person. First-year university students are particularly vulnerable to stress. The use of mindfulness-based programs to help students reduce and manage stress is gaining popularity around the world. Previous research has shown that such programs can improve the psychological well-being of students by reducing levels of anxiety and depression. In addition, students in helping majors, such as psychology students, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…It has been shown that various stress reduction techniques and mindfulness activities are practical and efficient in reducing psychological distress [ 45 ]. A non-randomized controlled trial among psychology undergraduates using a brief mindfulness training demonstrated significantly lower levels of depression and significantly higher levels of subjective happiness in the experimental group than the control group [ 46 ]. Clinical-year medical students had lower depression and anxiety scores compared to pre-clinical students.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that various stress reduction techniques and mindfulness activities are practical and efficient in reducing psychological distress [ 45 ]. A non-randomized controlled trial among psychology undergraduates using a brief mindfulness training demonstrated significantly lower levels of depression and significantly higher levels of subjective happiness in the experimental group than the control group [ 46 ]. Clinical-year medical students had lower depression and anxiety scores compared to pre-clinical students.…”
Section: Discussionmentioning
confidence: 99%